2018
DOI: 10.1016/j.cbpa.2018.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of lipid metabolism genes and the influence of fatty acid supplementation in the hepatic lipid metabolism of dusky grouper ( Epinephelus marginatus )

Abstract: Dusky grouper is an important commercial fish species in many countries, but some factors such as overfishing has significantly reduced their natural stocks. Aquaculture emerges as a unique way to conserve this species, but very little biological information is available, limiting the production of this endangered species. To understand and generate more knowledge about this species, liver transcriptome sequencing and de novo assembly was performed for E. marginatus by Next Generation Sequencing (NGS). Sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Therefore, proteolysis would be expected to be a key intestine-specific function among various amphioxus organs. It was also observed that some hepatic cecum-specific GO terms, such as those involving organic metabolism, are functions that have also been associated with the liver in other vertebrate species (Araújo et al, 2018). A large number of nerve cord–specific GO terms involving nervous system–related functions and development were represented, indicating that the nervous system of amphioxus is unexpectedly functionally complex with diverse function, as previously described (Benito-Gutiérrez, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, proteolysis would be expected to be a key intestine-specific function among various amphioxus organs. It was also observed that some hepatic cecum-specific GO terms, such as those involving organic metabolism, are functions that have also been associated with the liver in other vertebrate species (Araújo et al, 2018). A large number of nerve cord–specific GO terms involving nervous system–related functions and development were represented, indicating that the nervous system of amphioxus is unexpectedly functionally complex with diverse function, as previously described (Benito-Gutiérrez, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…These studies often use generic commercial diets, formulated for other marine fish species and include testing fish, crustacean-and mollusk-based moist diets (Araújo et al, 2018;Kerber et al, 2012;López & Castello-Orvay, 2003;Ramos et al, 2012;Sanches et al, 2007;Sousa et al, 2019). In addition, these studies mostly employed fish collected from the wild which may have affected grouper performance.…”
Section: Use Of Practical Diets Within Recirculatedwater Tank Production Systemsmentioning
confidence: 99%
“…The liver is responsible for several processes, such as immune response [16,17], detoxification [18], metabolism [19,20] and reproduction [21,22]. In the liver, the lipid metabolism is investigated to identify the genes and pathways involved in fatty acid synthesis, lipid transport and the oxidation process [23]. Numerous studies were conducted to understand the lipid metabolism in fish species exposed to different diets, toxic compounds or nanoplastics [24][25][26].…”
Section: Introductionmentioning
confidence: 99%